2010
DOI: 10.3393/jksc.2010.26.4.254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DCA on Cell Cycle Proteins in Colonocytes

Abstract: PurposeEvidence that indicates bile acid is a promoter of colon cancer exists. Deoxycholic acid (DCA) modifies apoptosis or proliferation by affecting intracellular signaling and gene expression. However, because previous studies have been based on studies on colon cancer cell lines, the effect of DCA on normal colonocytes is unknown.MethodsNormal colonocytes and Caco-2 and HCT116 cells were treated with 20 µM and 250 µM of DCA, and the effect of different concentrations of DCA was measured based on the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Recent studies demonstrated that microbiomes had strong effects on m6A modification and expression of m6A ‘writers’ in mouse brain and intestine . By consulting the literature, we found three intestinal flora metabolites that are most closely related to the development of CRC: Short‐chain fatty acids (butyrate), DCA and ursodeoxycholic acid . In the present study, we found that butyrate, a classical intestinal microbial metabolite, could decrease the level of m6A and down‐regulate the expression of METTL3 and CCNE1 in CRC cells.…”
Section: Discussionsupporting
confidence: 56%
“…Recent studies demonstrated that microbiomes had strong effects on m6A modification and expression of m6A ‘writers’ in mouse brain and intestine . By consulting the literature, we found three intestinal flora metabolites that are most closely related to the development of CRC: Short‐chain fatty acids (butyrate), DCA and ursodeoxycholic acid . In the present study, we found that butyrate, a classical intestinal microbial metabolite, could decrease the level of m6A and down‐regulate the expression of METTL3 and CCNE1 in CRC cells.…”
Section: Discussionsupporting
confidence: 56%
“…However, colonic BAs can reach concentrations of up to 1 mM in the colon following a high-fat meal and, in humans, these are mostly secondary BAs [8,9,12]. In contrast to the effect of low secondary BA concentrations, we and others have shown that secondary Bas, such as DCA, at physiological concentrations (0.05 to 0.3 mM), inhibit colonic cell proliferation to varying degrees based on the type of cell [10,61]. Specifically, DCA and LCA promote cell cycle arrest and apoptosis primarily through the generation of intracellular reactive oxygen species (ROS), genomic DNA breakage, activation of ERK1/2, caspase-3 and poly(ADP-ribose) polymerase (PARP), but decreased cyclin E concentrations [10,60,61].…”
Section: The Impact Of Secondary Bas and Scfas On Colonic Cell Promentioning
confidence: 99%
“…Histone deacetylase (HDAC) inhibitor. Binds GPR109A regulates gene expression, inflammation and autophagy Bifidobacterium Decreased in levels; having the anti-tumor activities Deoxycholic acid Activating β-catenin and epidermal growth factor receptor (EGFR) signaling [ 132 ] Clostridium Increased in levels; acting through FXR, PXR, VDR Lithocholic acid Promoting cancer invasion and MAPK signaling [ 136 ] Bacteroides fragilis Increased in levels Ursodeoxycholic acid Inhibiting the activation of COX-2 [ 146 ], blocking Ras activation [ 147 ] Decreased in levels Bacterial toxin (Fragilysin) Activating the β-catenin nuclear signaling [ 157 ] Bacteroides fragilis Increased in levels Trimethylamine-N-oxide (TMAO) Use L-carnitine or choline to produce TMAO [ 18 ] Clostridium Increased in levels …”
Section: Metabolic Role Of Gut Microbiotamentioning
confidence: 99%
“…DCA, one metabolite of the gut microbiota, has been known as a significant contributor to the development of CRC. There is evidence indicating that DCA could modulate intracellular signaling and gene expression [ 132 ]. DCA can induce cancer stemness by regulating the muscarinic 3 receptor/Wnt signaling pathway [ 133 ].…”
Section: Metabolic Role Of Gut Microbiotamentioning
confidence: 99%